The fourth order of accuracy sequential type rational splitting of inhomogeneous evolution problem - Rogava, J.; Tsiklauri, M. (Український математичний вісник, 2009)
In the present work symmetrized sequential type decomposition scheme of the fourth degree precision for the solution of inhomogeneous evolution problem is constructed. The fourth degree precision is reached by introducing the complex parameter α = 1/2 ± i(1/2√3) and by the approximation of the semigroup through the rational approximation. For the considered scheme the explicit a priori estimation is obtained.